An acid-pasting strategy towards PTCDA based high performance lithium/sodium ion battery cathodes. (20th June 2018) - Jing, Fan; Huang, Tao; Tao, Guangzhi; Ma, Lie; Lu, Deng; Liu, Ruili; Xi, Xin; Wu, Dongqing
Abstract: An acid-pasting approach is developed in this work to prepare the composites of 3, 4, 9, 10-perylenetetracarboxylic dianhydride (PTCDA) and carbon black (CB) by mixing both components in concentrated sulfuric acid. Different from the traditional powder processing, the solution-based fabrication strategy easily renders the effective combination of PTCDA and CB in the resultant CB/PTCDA composites, thus greatly improving their electrochemical performances. As the results, the composite with 20 wt% PTCDA shows excellent rate performances as the cathode material for both lithium ion battery (88 mAh g −1 at 5000 mA g −1 ) and sodium ion battery (100 mAh g −1 at 1000 mA g −1 ). As a facile and efficient processing strategy, the acid-pasting approach is expected to have wide application in the fabrication of organic electrodes in secondary batteries. Graphical abstract: An acid-pasting approach is developed to prepare the composites of 3, 4, 9, 10-perylenetetracarboxylic dianhydride and carbon black (CB/PTCDA). The solution-based fabrication strategy can greatly improve the electrochemical performances of the CB/PTCDA composites in both lithium ion battery and sodium ion battery.Image 1